Reset control for synchronization of multi-agent systems - Meng, Xiangyu (2021)
Standard approaches to synchronization problems in multi-agent systems apply local smooth control signals to achieve ultimate coherence. Most existing algorithms emphasize asymptotic behavior rather than transient performance. An alternative design framework based on reset control is presented to guarantee not only the asymptotic convergence but also a desired transient response. Specifically, the control protocol consists of a proportional integral (PI) compensator and a Clegg integrator (CI), where the integral term is reset to zero whenever the proportional term crosses zero. Numerical examples are included to illustrate the main result, and to compare the proposed reset control approach with the traditional static/dynamic state feedback control and the quasi-reset control methods.